Behaviour of bolted endplate composite joints to square and circular CFST columns. (April 2017) - Thai, Huu-Tai; Uy, Brian; Yamesri; Aslani, Farhad
Abstract: This paper presents the results of an experimental study on the structural performance of blind bolted endplate composite connections to concrete filled steel tubular (CFST) columns under static loading. Four full-scale sub-assemblages of cruciform composite joints representing the internal region of a composite frame were tested. The parameters varied were the shape of column sections and the type of endplates. The performance of the joints in terms of rotational stiffness, moment resistance and rotation capacity was evaluated to explore the effects of the shape of column sections and endplate types. An analytical model was also developed to predict the moment-rotation behaviour of composite joints. The experimental results indicated that both moment resistance and initial stiffness of the tested connections are considerably enhanced if the flush endplate and square column were replaced by the extended endplate and circular column, respectively. Highlights: Experimental tests on four full-scale composite joints were conducted. The effects of the shape of column sections and endplate types were examined. An analytical model was developed to predict the moment-rotation response of tested joints.